Plant Aromatic Prenyltransferases: Tools for Microbial Cell Factories. Issue 8 (August 2020) - de Bruijn, Wouter J.C.; Levisson, Mark; Beekwilder, Jules; van Berkel, Willem J.H.; Vincken, Jean-Paul
Abstract : In plants, prenylation of aromatic compounds, such as (iso)flavonoids and stilbenoids, by membrane-bound prenyltransferases (PTs), is an essential step in the biosynthesis of many bioactive compounds. Prenylated aromatic compounds have various health-beneficial properties that are interesting for industrial applications, but their exploitation is limited due to their low abundance in nature. Harnessing plant aromatic PTs for prenylation in microbial cell factories may be a sustainable and economically viable alternative. Limitations in prenylated aromatic compound production have been identified, including availability of prenyl donor substrate. In this review, we summarize the current knowledge about plant aromatic PTs and discuss promising strategies towards the optimized production of prenylated aromatic compounds by microbial cell factories. Highlights: Prenylation of aromatic compounds is an essential modification to enhance functionality of plant secondary metabolites, and many prenylated aromatic compounds possess health-beneficial bioactivities. A comprehensive overview of characterized plant aromatic PTs shows that most of these enzymes possess strict substrate- and regio-specificities. Knowledge gaps include the absence of high-resolution plant aromatic PT structures and lack of characterized plant aromatic O -PTs. Microbial cell factories expressing plant aromatic PTs have potential for biotechnological production of valuable bioactive compounds. Improving prenyl donor supply, and colocalization of plant aromatic PTs and substrates, have been identified as the current challenges that need to be addressed to increase prenylation yields.